Pengembangan Perpustakaan Online Pada Direktorat Jenderal Pencegahan dan Pengendalian Penyakit Kemenkes RI - Oktaviana, Shinta; Sukarsih, Sri (POLITEKNIK NEGERI JAKARTA, 2021)
With the development of technology, it is hoped that humans can innovate in helping work become faster and more effective. By making a conventional system into a computerized system. The existing library system at the Directorate General of Disease Prevention and Control of the Indonesian Ministry of Health is currently still using a manual or conventional system. In borrowing books, the borrower fills in personal data in the guest book and only provides a certificate, so it is less effective. Damage and loss of borrower data is vulnerable to occur. Therefore, it is necessary to develop an online library via a website, it is hoped that the development of an online library can provide maximum service to library users and in data processing can minimize errors. As well as making it easier for librarian such as monitoring the availability of books and recording requests. Access to borrow books is also easier.